Update on seizure and therapeutic drug monitoring in dogs and cats. Issue 1 (21st January 2022) - Green, Matt; Lowrie, Mark
Abstract : Background : Epilepsy is defined as the propensity to suffer recurring unprovoked epileptic seizures and is one of the most frequently encountered neurological complaints seen in veterinary practice. Effective management of these cases requires accurate identification and diagnosis, appropriate client communication, as well as regular monitoring of seizure progression and response to therapy. Aim of the article : This article provides an update on the diagnosis of epileptic seizures and how to manage such cases with use of anti‐epileptic drugs, including imepitoin, which is a relatively recent addition to the range of available therapies.